THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, WORK ETHIC, AND COMPENSATION ON EMPLOYEE PEFORMANCE - Adrie Oktavio; Agustinus Nugroho; Thomas Stefanus Kaihatu (ITB AAS Indonesia Surakarta, 2024)
Abstract Employee performance is the most important thing that must be achieved immediately by a company because by having good employee performance, all the company's visions and targets can be achieved easily. There are a number of factors that can influence employee performance. However, what researchers believe can influence significantly are the variables Organizational Commitment and Work Ethics as internal factors and Compensation as an external factor. This research is quantitative research with an explantory approach using primary data and questionnaire methods in data collection. The collected data was analyzed with smart PLS 3.0 software. The research results show that the Organizational Commitment variable, Work Ethics variable, and Compensation variable, each variable has a positive relationship and a significant influence on the Employee Performance variable because the P-Values value is below the level of significance and leads to positive direction Keywords: Organizational Cmmitment, Work Ethic, Compensastion, Employee Peformance